Determinants of sexual habits in Italian females. Issue 6 (December 1992) - Parazzini, F; Cavalieri d'Oro, L; Negri, E; La Vecchia, C
Abstract : OBJECTIVE–To identify characteristics of women reporting multiple sexual partners and early age at first intercourse in Italy. METHOD–Information on 1139 control women (median age 54 years) interviewed as part of a case-control study of cervical neoplasia conducted in the greater Milan area, Northern Italy were analysed using stratified analysis and multiple logistic regression. RESULTS–Overall, 81% of the study sample reported no more than one sexual partner, 10% two and 9% three or more. The proportion reporting multiple sexual partners tended to be higher among younger and more educated women (4% vs 19% of women with respectively less than 7 and 12 or more years of education reported three or more partners). Ever smokers reported a higher number of sexual partners than never smokers. The proportion of nulliparae reporting three or more sexual partners was higher than that of parous women. These findings were confirmed after taking into account in a multivariate analysis the role of potential confounding factors. Furthermore similar findings emerged from an analysis restricted to women aged 40 years or less. Always considering number of sexual partners, no relationship emerged with marital status, spontaneous or induced abortions, lifetime number of reported Pap smears and contraceptive habits. With reference to age at first intercourse, 25% of the study population reported their first intercourse at age 18 or before, 34% between 19 and 22 years, and 41% at age 23 or later. Younger women (that is, more recent cohorts) more frequently reported earlier age at first intercourse and the proportion of never married women reporting early intercourse was higher (51% vs 22% of never married vs married women). No relationship emerged between education, smoking habits, parity, history of spontaneous or induced abortions, number of Pap smears, contraceptive habits, and age at first intercourse. CONCLUSION–This study documents conservative sexual habits in Northern Italian females (at least on the basis of self reporting) but indicates that any educational compaigns towards safe sex should be focused towards younger women, particularly smokers, unmarried and nulliparae.